Egyptology, Theodore Roosevelt and Lord Carnarvon in the Poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2022)
It was Shawqi's right or rather his duty for which he was entrusted with his submissive talent, creativity, and ability to master the elements of poetry and the tools of art in addition to his strong patriotic sense and sincere national conscience to glorify the ancient civilization of Egypt. In this works, Shawqi praises Egypt’s monuments and its glory and indicates what happened to the ancient Egyptians who preceded him in the fields of science, art, building, architecture, engraving, painting, photography, and others. Shawqi referred to the pharaonic monuments in a group of his poems as part of a poem that has other purposes and in others as a complete poem with one purpose. This thinking indicates the extent of Shawqi's awareness of ancient Egyptian history, his familiarity with its events, and his use of Egyptian history in the service of poetic art.